Pages of Poison: Identifying 19th Century Arsenical Green Books at Queen’s University Library - Bell, Kim; Canham, Robin (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2025)
In the 19th century, arsenic was a commonly used additive and colourant found in paper, clothing, household goods, personal products, and even confectionary items. Although most of these toxic products have long been removed from public consumption, books created using copper acetoarsenite, a green pigment, remain in our libraries and personal collections, with potential health implications. This article focuses on identifying 19th-century books in the Queen’s University Library, Kingston, suspected to contain copper acetoarsenite or emerald green. Based on visual identification, 150 books published between 1797 and 1900 were selected from the collections for X-ray fluorescence (XRF) spectroscopy testing to detect the arsenical colourant. Results revealed that 28 books tested contained significant amounts of arsenic in their bookcloth, covering paper, surface decoration, endpapers, or fore-edges.These findings underscore the necessity to implement proper handling and storage protocols and conservation strategies to mitigate the risk of arsenic exposure to library staff, researchers, and patrons. Moreover, this research contributes to the broader understanding of arsenic’s impact on cultural heritage preservation, highlighting the importance of interdisciplinary collaboration between librarians, conservators, archivists, historians, and scientists. By documenting and addressing arsenic contamination in library collections, institutions can safeguard the well-being of individuals interacting with these materials while preserving these cultural heritage items for the future.